Musical Characteristics of the Pingxian Folk Song as Cultural Narrative - Jing, Yang; Theerapan, Suthasinee; Chuangprakhon, Sayam; Chaiyason, Noppon; Jungate, Kittikun; Wenying, Chen (Resital: Jurnal Seni Pertunjukan, 2025)
This study aims to analyze the musical characteristics of the Pingxian Folk Song in Ping’an District, Qinghai Province, with a particular focus on its function as a cultural narrative. Employing a qualitative methodology, the research integrates ethnomusicological analysis, field observations, and interpretive frameworks to examine four key dimensions: lyrical structure and language use, rhythmic patterns and vocal ornamentation, melodic and modal systems, and cultural symbolism embedded in performance contexts. Findings indicate that Pingxian folk songs exhibit a distinct lyrical form known as the “3.5-line structure,” incorporating hybrid use of Mandarin and local dialects that reflect regional linguistic identity. The flexible rhythmic style, often governed by breath and emotion, is supported by the traditional use of Paiban as a percussive timing device. Melodic lines follow a modal system capable of symbolic modulation, such as transitions between Bb Gong and C Shang Qingyue, to express shifts in emotional and ritual states. Culturally, the songs encode ethnic memory and social values through symbolic narratives referencing local myths, ancestral figures, and natural imagery. Performances are deeply embedded in ritual, seasonal festivals, and informal educational settings, thereby serving as dynamic vehicles for the transmission of intangible cultural heritage. These musical features collectively affirm the role of Pingxian Folk Song as a medium for maintaining ethnic identity and cultural continuity. The study highlights the necessity of understanding folk music as both sonic art and cultural practice. It is recommended that future research explore comparative modal systems across folk traditions in the Hehuang cultural region and investigate the integration of Pingxian folk elements into contemporary educational and digital platforms to support sustainable heritage preservation.